Proposed Hybrid Cryptographic Technique To Secure Data In Web Application - Gupta, Neha; Kapoor, Vivek; Haweliya, Jyoti (International Journal of Computer Sciences and Engineering, 2019)
Web applications are becoming a necessary part of modern life. Security is one of the most important non-functional requirements of every solution. Early days, security and data privacy was just luxury part of software development and it was an optional requirement but nowadays it plays a critical role in daily life. This research paper has been made to observe the need for security algorithms in web application. This work observes that the current security level of existing applications and also recommend improved security solutions to enhance the security level as well performance of proposed architecture. This work recommends that ECC (asymmetric key cryptography) and Blowfish algorithm (symmetric key cryptography) can be used to achieve confidentiality during communication. It also considers the MD5 algorithm to maintain the integrity and modified Kerberos algorithm to achieve authentication. The complete work will propose a security architecture having solution to achieve confidentiality, integrity with strong authentication policy for web application development.